Review paperThe role of extracellular matrix metalloproteinases and their inhibitors in allergic diseases - Kuźmiński, Andrzej; Przybyszewski, Michał; Graczyk, Małgorzata; Bartuzi, Zbigniew (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2012)
During the migration to the site of inflammation, allergic inflammatory cells must overcome several structures that constitute an impregnable barrier under normal conditions. One such structure is the extracellular matrix responsible for closely filling the intercellular space of tissues. The loosening of this tight structure by the activity of specific tissue enzymes, i.e. extracellular matrix metalloproteinases (MMPs), enables the influx of effector cells to the site of inflammation, thus facilitating the development of allergic inflammation and sustaining its presence. Specific tissue inhibitors of metalloproteinases (TIMPs) represent the most important factor involved in the regulation of MMP activity. Under physiological conditions, MMPs and TIMPs co-exist in a particular specific equilibrium, which is disturbed under pathological circumstances. The MMP-2 and MMP-9, referred to as gelatinases, belong to the best-studied MMPs associated with the development of allergic disorders. Their role pertains to the degradation of type IV collagen, the main component of basal membranes; this facilitates the influx of cells to the site of allergic inflammation.